(untitled) (KULT_online, 2009)
In this volume from the series "Literalität und Liminalität" (Literacy and Liminality), editors Achim Geisenhanslüke and Georg Mein survey a relatively recent field that combines theories of written language and the increasingly prominent concept of liminality. The editors tap a broad range of disciplines – including literary and media studies, the philosophy of language, psychoanalysis, and even mathematics – in which the interconnections between writing and metaphysical thresholds and transition states are currently being explored. The resulting collection is thoroughly heterogeneous but rarely loses site of its primary focus. While the contributors’ combined efforts do not yield a unitary outcome, they do offer a panoramic view of a variegated and fascinating research landscape that invites further exploration.